2020
DOI: 10.3390/plants9111561
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Morphological Characteristics and Determination of Different Patterns for Rubber Particles in Dandelion and Different Rubber Grass Varieties

Abstract: Russian dandelion Taraxacum kok-saghyz (TKS) is one promising alternative crop for natural rubber production. However, it is easily confused with other dandelions. In this study, we performed a systematical comparison of the morphological characteristics for different TKS varieties and common dandelion Taraxacum officinale (TO). Our results demonstrated that several obvious differences in morphology can be found between TKS and TO. TO leaf is a pinnate shape, its margin is heavily jagged and its base is cuneat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…In comparison to other commercial rubbers, the international research on DR is still in its early stages, with the current focus primarily on increasing yield through breeding, molecular research, and extraction processes 25–30 . Researchers have shown confidence in ridge cropping as a means to boost yield, and future breeding research is suggested to concentrate on optimizing DR cultivation production and management 31 .…”
Section: Rubbermentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to other commercial rubbers, the international research on DR is still in its early stages, with the current focus primarily on increasing yield through breeding, molecular research, and extraction processes 25–30 . Researchers have shown confidence in ridge cropping as a means to boost yield, and future breeding research is suggested to concentrate on optimizing DR cultivation production and management 31 .…”
Section: Rubbermentioning
confidence: 99%
“…23 In 2016, some researchers successfully developed the precise quantitative technology for the fabrication of small rubber particle protein and natural rubber precursor substances, thus laying the foundation for the in vitro biosynthesis of DR. 24 In comparison to other commercial rubbers, the international research on DR is still in its early stages, with the current focus primarily on increasing yield through breeding, molecular research, and extraction processes. [25][26][27][28][29][30] Researchers have shown confidence in ridge cropping as a means to boost yield, and future breeding research is suggested to concentrate on optimizing DR cultivation production and management. 31 Regarding the molecular synthesis mechanism, a comprehensive understanding of the specific functions and interactions of individual genes or proteins in DR has not yet been fully achieved.…”
Section: Dandelion Rubber (Dr)mentioning
confidence: 99%
“…Multiple past efforts to achieve U.S. natural rubber independence were unsuccessful, because they were funded mostly during supply chain crises [ [3] , [4] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] ]. The “Emergency Rubber Project” of WWII cultivated alternative NR-producing plants, with major plantings of guayule, rubber dandelion and Madagascar rubber vine [ 28 ], but the program was abandoned after Southeast Asian supply lines reopened.…”
Section: Introductionmentioning
confidence: 99%
“…Unique traits can be used to differentiate between different clones/species [9][10]. The difference in leaf size, leaf area, leaf length and width ratio, leaf angle was assessed as significantly different among different clones so that it could be used as a marker in clone identification [11]. In this research, several improvements have been made in leaf sampling, measurement of leaf samples using the leafgram method, and adding measured leaf samples to improve accuracy in assessing the observed characters.…”
Section: Introductionmentioning
confidence: 99%